Integrating Ecological Values into Arabic Muhadatsah Learning to Promote Students’ Ecological Awareness - Harpan Masdar MT; Sulaeman Sulaeman; Nur Fadilah Amin (Universitas Islam Negeri Palangka Raya Raya, 2026)
The integration of sustainability into language education has received increasing scholarly attention; however, Arabic language instruction has rarely been positioned as a medium for fostering students' ecological awareness. This study investigates the effectiveness of integrating ecological values into Arabic muhadatsah learning to promote ecological awareness among students at an Islamic senior secondary school. Employing a Classroom Action Research design based on the Kemmis and McTaggart model, the study was conducted over two instructional cycles involving 35 tenth-grade students at MA Mursyiduttullab Lembanna. Data were collected through classroom observations, semi-structured interviews, and a 20-item ecological awareness questionnaire and analyzed using descriptive statistics, paired-sample t-tests, thematic analysis, and effect size analysis. The findings indicate that contextual muhadatsah activities incorporating authentic environmental themes significantly enhanced students' ecological awareness, classroom participation, and communicative confidence. The intervention also encouraged students to internalize environmental responsibility through dialogue, collaborative interaction, and reflective communication. These findings demonstrate that Arabic communicative learning can function not only as a means of developing speaking proficiency but also as a pedagogical space for cultivating sustainability values. This study contributes to the intersection of Arabic language pedagogy, ecolinguistics, and Education for Sustainable Development by proposing a contextual and sustainability-oriented muhadatsah model that integrates language learning with ecological value formation.